Breakdown, breakthrough : the professional woman's guide to claiming a life of passion, power, and purpose - Caprino, Kathy, 1960- (BK life book., 2008)
Many women who are outwardly "successful" in their professions have awakened to the realization that their work is no longer positive, meaningful, or productive in their lives. Caprino's book sheds light on this growing epidemic of disempowerment and offers a way out.